Perceptions and Experiences of Grade 6 Pupils on the Awareness Prayer - Eva Mae A. Canoy; Shylene Marie T. Lumbab; Rachell Anne M. Taneo (Indonesian Journal of Christian Education and Theology, 2026)
Prayer is part of a Christian’s way of life but overly structured routines can lose personal meaning, especially for pupils with limited ability to reflect on God’s presence. This study aims to explore the perceptions and experiences of Grade 6 students on the Awareness prayer as an alternative prayer routine of finding God in all things aside from routinary prayers. The process of exploration follows the descriptive research design using quantitative and qualitative data from a sample of Grade 6 students. Results show gratitude as the dominant perception, with students practicing breathing and focused thoughts. However, many struggled to pause and imagine God’s presence. Recommendations include enhancing mental and emotional engagement through level-appropriate strategies and teacher training